Enhancement of agri-food by-products: green extractions of bioactive molecules with fungicidal action against mycotoxigenic fungi and their mycotoxins - Giorni, Paola; Bulla, Giulia; Leni, Giulia; Soldano, Mariangela; Tacchini, Massimo; Guerrini, Alessandra; Sacchetti, Gianni; Bertuzzi, Terenzio (Frontiers in Nutrition, 2023)
Nowadays, alternative strategies, based on the use of bioactive compounds, have been proposed to reduce mycotoxin contamination and limit the use of chemical fungicides. In the present work, several by-products collected from the agri-food chain have been subjected to green extraction protocols (i.e. steam distillation, ultrasound-assisted and Naviglio® extraction) to recover extracts rich in polyphenols and terpenes. Each extract has been in vitro assessed for its ability to inhibit the development of the main mycotoxigenic species and related mycotoxins. A. flavus and A. carbonarius were appreciably reduced by pear (from -45 to -47%) and grape marc (from -21 to -51%) extracts, while F. graminearum was demonstrated to be highly influenced by grape stalks, pear and grape marc extracts (- 24% on average). On the contrary, F. verticillioides was inhibited only by pear (-18%) and at a very low and negligible extend by apple (-1%) and green beans (-3%). As regards the mycotoxin reduction, the extracts resulted to inhibit OTA from 2% to 57%, AFB1 from 5% to 75% and DON from 14% to 72%. The highest percentages of reduction were obtained against FBs (from 11% to 94%), ZEN (from 17 to 100%) and from Alternaria toxins (from 7 to 96%). In conclusion, this work provided promising results in the production of bioactive extracts obtained from agri-food by-products, which could be exploited as potential biofungicides against the development of mycotoxigenic fungi and related mycotoxins.